THE INFLUENCE OF CAPITAL STRUCTURE AND ASSET MANAGEMENT ON PROFITABILITY AND FIRM VALUE (AN EMPIRICAL RESEARCH AT REAL ESTATE AND PROPERTY THAT LISTED IN INDONESIA STOCK EXCHANGE FOR THE PERIOD OF 2011-2013) - Agustiningtias, Eka; Kertahadi, Kertahadi; Suyadi, Imam (Profit: Jurnal Adminsitrasi Bisnis, 2016)
The objectives of the research are to analyze the influence of capital structure and asset management on profitability and firm value of real estate and property that listed in Indonesia Stock Exchange for the period of 2011-2013 and give recommendations as the completion upon this research. By applying Generalized Structured Component Analysis (GSCA) of the population consisted of 54 company and a sample of 30 company was taken in 3 years observation, the analysis attempts to examining the influence among variables. This research uses debt ratio (DR), debt to equity ratio (DER),) as the variables of capital structure, inventory turnover (ITO, fixed asset turnover (FATO) and Total asset turnover (TATO) as the variable of asset management, and price book value (PBV), closing stock price as the variable of firm value. Result of the research reveal that capital structure has a significant and positif influence on profitability, asset management has no significant and positif influence on profitability, capital structure has a significant and positif influence on firm value, asset management has no significant and positif inflence on profitability. Furthermore profitability has a significant and positif influence on firm value. The present research confirms that capital structure, asset management, profitability and firm value is the essential and important aspect for the investors in determining the profitable stocks. Therefore, it is very useful for the investors to considerate these variable of research in order to make the right investment decisions and do stock trading confidently.Keywords: Capital Structure, Asset Management, Profitability, Firm Value, Real Estate and Property, GesCA, Indonesia Stock Exchange (IDX)